Dave Cook of the Rockies, frontier general, fighting sheriff, and leader of men - Collier, William Ross; Westrate, Edwin Victor (New York, R. R. Wilson, incorporated, 1936)
frontier general fighting sheriff
Keywords: Cook, D. J. -- 1840-1907.; Criminals -- West (U.S.); Frontier and pioneer life -- West (U.S.)